2007
DOI: 10.1016/j.freeradbiomed.2007.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide receptor signaling in murine macrophages is linked to reactive oxygen species generation

Abstract: Macrophage activation is critical in the innate immune response and can be regulated by the nucleotide receptor P2X 7 . In this regard, P2X 7 signaling is not well understood but has been implicated in controlling reactive oxygen species (ROS) generation by various leukocytes. Although ROS can contribute to microbial killing, the role of ROS in nucleotide-mediated cell signaling is unclear. In this study, we report that the P2X 7 agonists ATP and 3′-O-(4-benzoyl) benzoic ATP (BzATP) stimulate ROS production by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 63 publications
(146 reference statements)
7
81
0
Order By: Relevance
“…Similarly, we have observed that stimulation of the MAP kinases ERK1/2, p38, and c-Jun N-terminal kinase (JNK) in the murine macrophage cell line RAW 264.7 by P2X 7 agonists is sensitive to antioxidants, suggesting that ROS may play a more global role in P2X 7 signaling [21]. Although P2 receptor potentiation of ROS production has been seen with several immune cell types, the role of P2X 7 in nucleotidedependent ROS production in macrophages is less well known.…”
Section: P2x 7 Activation Mediates Nadph Oxidase-dependent Ros Producmentioning
confidence: 82%
See 4 more Smart Citations
“…Similarly, we have observed that stimulation of the MAP kinases ERK1/2, p38, and c-Jun N-terminal kinase (JNK) in the murine macrophage cell line RAW 264.7 by P2X 7 agonists is sensitive to antioxidants, suggesting that ROS may play a more global role in P2X 7 signaling [21]. Although P2 receptor potentiation of ROS production has been seen with several immune cell types, the role of P2X 7 in nucleotidedependent ROS production in macrophages is less well known.…”
Section: P2x 7 Activation Mediates Nadph Oxidase-dependent Ros Producmentioning
confidence: 82%
“…For example, reports by our lab and others have shown that P2X 7 activation results in ROS production, which may act as a second messenger in several P2X 7 agonist-induced events [16,17,21,52,53]. However, the mechanisms by which P2X 7 promotes ROS production are less well understood, and ROS generation in response to P2X 7 agonists has not been demonstrated in primary cells.…”
Section: P2x 7 Modulation Of Innate Immunitymentioning
confidence: 95%
See 3 more Smart Citations